Preparation, Physicochemical Properties and In Vitro Antimicrobial Acitvities of Oligochitosan Against Fusarium Moniliforme and Ralstonia Solanacearum - Nguyen Dao Thanh, Huong; Le Thanh, Binh; Do Thi Mai, Trinh; Nguyen Van, Vinh (Journal of Technical Education Science, 2025)
This study focuses on the synthesis and characterization of oligochitosan and its potential antimicrobial properties. Oligochitosan was produced by dissolving chitosan in 2% acetic acid and degrading it with 3% hydrogen peroxide at 60 °C for 4 h, resulting in a product with a molecular weight of 7.92 kDa. The antimicrobial effects were tested against the fungal pathogen Fusarium moniliforme and the bacterial pathogen Ralstonia solanacearum under in vitro conditions. The results indicated that oligochitosan demonstrated a concentration-dependent antifungal activity, achieving up to 60.17% inhibition of mycelial growth at 2000 ppm, which was higher than the inhibition observed with chitosan. However, neither chitosan nor oligochitosan exhibited antibacterial effects against R. solanacearum. The findings suggest that oligochitosan holds promise as an effective antifungal agent, though its antibacterial activity remains negligible. These results support the application of oligochitosan in agricultural and biological control, particularly for plant disease management.